2016
DOI: 10.1038/srep24520
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of the IQD gene family in moso bamboo (Phyllostachys edulis)

Abstract: Members of the plant-specific IQ67-domain (IQD) protein family are involved in various aspects of normal plant growth and developmental processes as well as basal defence response. Although hundreds of IQD proteins have been identified, only a small number of IQDs have been functionally characterized. Moreover, no systematic study has been performed on moso bamboo. In this study, we performed for the first time a genome-wide identification and expression analysis of the IQD gene family in moso bamboo. We ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 57 publications
2
63
0
Order By: Relevance
“…In this study, the expression levels of all 20 selected GhIQD genes were increased ( Fig. 6) in response to MeJA treatment, which is consistent with previous studies showing that most of the IQD genes in P. trichocarpa and moso bamboo are induced by MeJA treatment [8,18]. These results imply that the IQD gene family plays an important role in tolerance to MeJA abiotic stress in plants.…”
Section: The Ghiqd Gene Family Expanded By Segmental Duplicationsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, the expression levels of all 20 selected GhIQD genes were increased ( Fig. 6) in response to MeJA treatment, which is consistent with previous studies showing that most of the IQD genes in P. trichocarpa and moso bamboo are induced by MeJA treatment [8,18]. These results imply that the IQD gene family plays an important role in tolerance to MeJA abiotic stress in plants.…”
Section: The Ghiqd Gene Family Expanded By Segmental Duplicationsupporting
confidence: 91%
“…A number of IQD genes have been reported in different plants; there are 33 AtIQD genes in A. thaliana, 28 OsIQD genes in Oryza sativa [16], 38 PtIQD genes in Populus trichocarpa [8], 29 PeIQD genes in Phyllostachys edulis (moso bamboo) [18], 67 GmIQD genes in Glycine max [19], and 34 SlSUN/IQD genes in Solanum lycopersicum [20]. In this study, a total of 102 GhIQD genes were identified in G. hirsutum L. The number of IQD genes in G. hirsutum L. is greater than that found in other plant species, possibly because G. hirsutum L. is an allotetraploid cotton species that originated from the hybridization of G. arboreum and G. raimondii and subsequent polyploidization 1-2 million years ago [25].…”
Section: The Ghiqd Gene Family Expanded By Segmental Duplicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge of the CaM/CML targets and of their biochemical functions and underlying biological processes will be imperative for deciphering CaM-mediated Ca 2+ signal transduction in plants (Yang and Poovaiah, 2003). Plant-specific IQD gene families, first annotated in Arabidopsis and rice and more recently in five additional species (Filiz et al, 2013;Huang et al, 2013;Feng et al, 2014;Ma et al, 2014;Wu et al, 2016), possibly encode the largest class of CaMBPs in plants. Although the roles of a few IQD members are beginning to emerge, the precise molecular functions and mechanisms of action are still elusive for any IQD protein .…”
Section: Discussionmentioning
confidence: 99%
“…The 33 IQD proteins of Arabidopsis are highly diverse in length (103-794 amino acids) and cluster in four major phylogenetic clades that differ mainly in the presence and distribution of family-specific motifs flanking the central IQ67 domain . Extensive IQD families (23-67 genes) have been annotated in rice (Oryza sativa; Abel et al, 2005) and recently in purple falsebrome (Brachypodium distachyon; Filiz et al, 2013), tomato (Solanum lycopersicum; Huang et al, 2013), soybean (Glycine max; Feng et al, 2014), poplar (Populus trichocarpa; Ma et al, 2014), and moso bamboo (Phyllostachys edulis; Wu et al, 2016). Thus, IQD proteins are possibly the largest class of CaMBPs in plants; however, their precise biological roles and biochemical functions remain to be elucidated van der Knaap et al, 2014).…”
mentioning
confidence: 99%